Synergistic Impact of Basil Extract (Ocimum basilicum) and Levofloxacin on the (Journal of the College of Basic Education, 2025)
This work intended to investigate on the effectiveness of total flavonoids as well as crude basil extract on the biofilm formation inhibition and also to determine the interaction of these compounds with Levofloxacin (Lfx) against biofilms developed by E.coli isolates Total flavonoids extractions was carried out using 75% methanol while crude basil extract using 100% methanol. One hundred nineteen clinical stool and urine Specimens collected from patients attending medical city hospital, Baghdad, Iraq. Out of 76 isolates, that hit in the Vitik 2 assay as E.coli, only 46 of these isolates formed biofilm when cultured in microtitre plates. Molecular detection was performed to determine whether the bacterial isolates harbour genes that predict the formation of biofilms. The bacterial strains were selected based on their ability to form biofilm and sundry other factors including, antibiotic resistance. The objectives showed that 21 (70%) of the isolates contain the fimH gene, while 17 (56.6%) out of the isolates had the pap gene for E.coli. The research showed that the crude extract had a higher antibiofilm effect than flavonoids with a concentration of 512 µg/mL. The results which were obtained showed that co-administration of Levofloxacin (8 µg/ml) and the crude extract (128µg/ml) offered considerable inhibition of biofilm formation of E. coli with an inhibition percentage of 88%. The flavonoids tested against E. coli in combination with Levofloxacin had inhibition concentrations of 128 µg/ml while Levofloxacin was 8 µg/ml giving inhibition ratio of 81.1%. This proved to exhibit additional synergistic action against bacterial biofilm formation at sub-to-micromolar concentrations. These consequences imply that in future this medication can be used to treat E. coli biofilm infection and act as antibacterial drugs. The findings of current study clarified the Synergistic Impact of Basil Extract and Levofloxacin on the Proliferation and Biofilm Development of E. coli .And prove that it restricted this development.